Evaluation of the acute effects of cigarette smoking on the eye of non-Smoking healthy young male subjects by optical coherence tomography angiography. (2nd April 2020) - Kaymaz, Abdulgani; Ulaş, Fatih; Toprak, Güvenç; Uyar, Enes; Çelebi, Serdal
Abstract: Purpose: Investigation of the acute effects of cigarette smoking on the eye using optical coherence tomography angiography (OCTA) on young healthy non-smoking male subjects. Materials and methods: The right eye of 25 healthy non-smoking male subjects were included in this study. Selected parameters of the macular and circumpapillary vasculature were measured, including macular flow indices, foveal avascular zone, vessel densities of macula and optic disc using OCTA. The measurements of the subjects were performed on the first day without smoking at 0 min, 5 min, 30 min and 60 min. Measurements were repeated at the same regime on the second day after smoking. Paired samples t -test and repeated measures one-way analysis of variance test was used for the statistical analysis. Results: The repeated measures analysis of variance test using the Bonferroni adjustment demonstrated a significant change for superficial and deep foveal vessel density, flow area of choriocapillaris, and circumpapillary capillary density following smoking (range of p value was <0.001–0.004). Intraocular pressure, foveal avascular zone area, flow area of outer retina and foveal non-flow area of superficial layer measurements did not have any significant changes following smoking (range of p value was 0.192–0.812). Conclusion: In non-smoking cases, even smoking only one cigarette significantly decreased the vessel density parameters at the acute period. Even though there was an increase in measured parameters shortly after smoking, it had lessened when compared to non-smokers, even one hour following smoking.